Probabilistic slope stability of alluvial materials in Maruni River, Papua, using MC-LHS and Bishop-Spencer methods - Lamma, Louis Hermanus; Setiawan, Arif; Valderama, Aldi Fariz; Aras, Firwansyah; Paradida, Yulia Putri (Journal of Degraded and Mining Lands Management, 2026)
The Maruni River in Manokwari Regency is one of the locations with sand and gravel resources, which are used as raw materials for infrastructure development. In the vicinity of the river, there is a slope with a steep inclination (>60°) and a height of approximately 8 m, which exhibits indications of minor landslides, suggesting potential instability. This condition necessitates a more comprehensive evaluation of slope stability. Therefore, this study aimed to evaluate slope stability using a probabilistic approach to obtain a more representative assessment of failure risk. The analysis was conducted using the Bishop and Spencer methods, combined with Monte Carlo (MC) and Latin Hypercube Sampling (LHS) techniques. Distribution tests were conducted for the cohesion, internal friction angle, and bulk density parameters of the original soil using Kolmogorov-Smirnov (KS), Akaike Information Criterion (AIC), and Bayesian Information Criterion (BIC). Based on the analysis, it is recommended to choose the Lognormal distribution for cohesion and internal friction angle, while the Normal distribution is more suitable for specific gravity. The findings indicate that the slope is marginally stable because its safety factor is approximately (close to) one, and the probability of failure does not decrease significantly. In stability assessment, the Spencer method provides a higher safety factor than the Bishop method; in addition, the LHS technique shows greater sensitivity than the MC method. Therefore, the application of probabilistic analysis with the integration of the Spencer method is considered more effective for evaluating slope stability.